Loose Financial Conditions, Rising Leverage, and Risks to Macro-Financial Stability - Barajas, Adolfo; Choi, Woon.; Gan, Ken.; Guerin, Pierre (Washington, D.C. : International Monetary Fund, 2021)
After a steady increase following the global financial crisis, private nonfinancial sector leverage rose further during the COVID-19 on the back of easy financial conditions induced by unprecedented policy support. We investigate the empirical relationships between increased leverage, financial conditions, and macro-financial stability in a sample of major advanced and emerging market economies. We find that loose financial conditions contribute to leverage buildups and generate an intertemporal tradeoff: financial stability risk is lessened in the near term but exacerbated in the medium term. The tradeoff is amplified during credit booms, when debt service burdens are particularly high, or when the share of foreign currency debt is high in emerging markets. Selected macroprudential tools can arrest leverage buildups and mitigate the tradeoff.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Banks; Depository Institutions; Micro Finance Institutions; Monetary Policy; Mortgages